Ultrastructural organization of pulmonary hemomicrovasculature in case of experimental acute renal failure - Zaiats, L. M.; Klishch, I. P.; Zukow, W. (Journal of Education, Health and Sport, 2018)
In our experiments on white male rats of Vistar line, we studied in dynamics (12, 24, 72 hours) the ultrastructural changes of pulmonary hemomicrovasculature in case of experimental acute renal failure. It has been determined that already in 12 hours after beginning of the experiment one can observe the ultrastructural constitution disorder of pulmonary hemomicrovasculature. In the capillary blood vessels of alveolar wall is determined the increased quantity of leukocytes, their adhesion and aggregation. With increase of the experimental period (24-72 hours), we have observed both dystrophic-destructive and compensatory-adaptive changes in pulmonary hemomicrovasculature.